Microeconomics - Gravelle, Hugh.; Rees, Ray (Harlow, England : FT/Prentice Hall, 2004)
A comprehensive exposition of modern microeconomic theory, beginning at the intermediate level and ending at an appropriate level for graduate students.
Includes bibliographical references and index.
oif 17/04/15
Loan
Keywords: Microeconomics